cGAMP-adjuvanted multivalent influenza mRNA vaccines induce broadly protective immunity through cutaneous vaccination in mice - Wandi Zhu; Lai Wei; Chunhong Dong; Ye Wang; Joo Kim; Yao Ma; Gilbert X. Gonzalez; Bao-Zhong Wang (Elsevier, 2022)
Increasing preclinical and clinical results have demonstrated that mRNA vaccines efficiently prevent infectious diseases and are safe in animal models and humans. In this study, we fabricated a multivalent influenza mRNA lipid nanoparticle (LNP) vaccine with mRNAs of hemagglutinins from influenza H1N1 and H3N2 viruses, matrix protein 1, and nucleoprotein. We found that cutaneous immunization with mRNA LNPs induced strong Th1 and Th2 cellular immunity with robust antigen-specific antibody titers and increased cytokine-secreting splenocytes and antibody-secreting cells. The supplement of cGAMP improved the immunogenicity of mRNA LNPs. Compared with αGC or cGAMP/αGC adjuvanted mRNA LNP formulations in our study, cGAMP mRNA LNPs induced more robust antibody responses. Enhanced cellular immunity with more IL-4 and IFN-γ secreting cells and effector memory T cell populations in spleens, as well as increased CD4+ resident memory (TRM) T cells in lungs were observed in cGAMP mRNA LNPs immunized group. These results demonstrated that cGAMP is an effective adjuvant for cutaneous vaccination of multivalent mRNA LNP vaccines in mice to induce stronger immune responses in the spleen and lung, and the cGAMP-adjuvanted mRNA LNPs protected against homologous and heterologous viral infection.